The European research collaboration for Children's Interstitial Lung Disease (ChILDEU) ERS Clinical Research Collaboration. Issue 6 (6th December 2018) - Cunningham, Steve; Gilbert, Carlee; Schwerk, Nico
There are over 200 conditions collectively assigned as children's interstitial (or diffuse) lung disease (ChILD), with a prevalence of 1.5 [1] to 3.6 [2] per million children per year. The conditions individually are rare to ultra-rare and are lumped for convenience [3], but studies need larger cohorts for each condition, in order to deliver progress. As most university hospitals see between one and five new ChILD cases each year [4], progress is slow unless international co-operation is in place. Enhanced clinical, parent, academic and industry engagement in the field of children's interstitial lung diseases will help improve case ascertainment, mechanisms and therapeutic developments for these ultra-rare conditions http://ow.ly/SM0I30mC3Jk